Determination of lower extremity peripheral artery disease: The role for automated Oscillometric measurement of ankle brachial index in Nigerians - E M Umuerri; V A Josephs; A O Obasohan (Nigerian Postgraduate Medical Journal, 2013)
Aims and Objectives : To determine the prevalence of LEAD and compare the accuracy of ABI obtained by automated oscillometric method with Doppler ultrasonography. Patients and Method s: This study compared the accuracy of ABI obtained by automated oscillometric method versus that by Doppler among 153 hypertensive patients aged 18 years and above, attending the hypertension clinic of the University of Benin Teaching Hospital, Benin-City. Results : Of the 153 patients studied, 64 (41.8%) and 48 (31.4%) had ABI <0.9 using hand held Doppler ultrasound and automated oscillometric method respectively, while 39 (25.5%) had LEAD detected by both methods. Assuming the gold standard for diagnosis of LEAD was by Doppler ABI <0.9, ABI obtained by automated oscillometric method had a sensitivity, specificity, positive and negative likelihood ratios of 60.9%, 89.9%, 6.03 and 0.43 respectively while the area under the receiver operating characteristic curve was 0.787. There was good and positive correlation between ABI obtained by automated oscillometric method and Doppler ultrasound with a Pearson′s correlation coefficient of 0.73 and 0.74 for left and right lower limbs respectively (p<0.001) Conclusion: ABI obtained using automated oscillometric method is a good alternative to Doppler ultrasonography when screening for LEAD.